Helicoverpa zea (Lepidoptera: Noctuidae) In-Season and Overwintering Pupation Response to Soil Type. Issue 1 (20th December 2022) - Dillard, DeShae; Reisig, Dominic D; Reay-Jones, Francis P F
Abstract: Heliothinae soil pupation is understudied despite the key role this life stage plays in their development. Many Heliothinae are important agricultural pests and understanding the interplay of environment and pupation is important to optimize pest management tactics oriented toward pupae. We studied the impact of three soil types (coarse sand, high organic muck, and fine-textured clay) on Helicoverpa zea (Boddie) in-season and overwintering pupal survivorship, diapause, depth, and weight in at two locations (North and South Carolina). We introduced wild-collected (in-season) and laboratory-reared (over the winter) infestations of H. zea larvae to each of the three soils and later excavated pupae. In-season and over the winter pupal survivorship was lower in fine-textured clay soils than in coarse sand or high organic muck. In addition, pupal depth and weight, in-season and over the winter, varied significantly by soil type. In general, depth was the shallowest, and pupae weight was lower when recovered from fine-textured clay soils. Finally, diapausing characteristics varied significantly by location and year, likely impacted by differing environmental conditions. Our results suggest that fine-textured clay soils negatively impact Heliothinae pupation and may be suppressing populations in areas with these soil types.